Recovering Nussbaum’s Aristotelian Roots (Cultura Económica, 2019)
The paper examines the relationship between Creating Capabilities and political liberalism. Originally founded on the basis of Aristotelian philosophy, the theory of ‘capabilities’ developed by Nussbaum turns to political liberalism in the mid 90’s. Throughout the article, the principles of both perspectives are depicted and contrasted, focusing on the capacity of affiliation, the concept of common good and the idea of freedom. Severine Deneulin argues that the current reality calls for the capabilities approach to be more rooted in a relational anthropology which the Aristotelian ethical tradition is more akin to. This line can be found in Nussbaum’s first approach to the theory of capabilities, where affiliation as an architectonic capability leads to the common good being the end of political action, and practical reason as an architectonic capability leads to reasoning ordered towards the achievement of the common good, tothe detriment of individualism.
Keywords: CAPABILITIES; POLITICAL LIBERALISM; ARISTOTLE; MARTHA NUSSBAUM; ETHICS